POTENSI VEGETASI HUTAN MANGROVE DI WILAYAH PESISIR PANTAI DESA KHATULISTIWA KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG - Lisna Lisna; Adam Malik; Bau Toknok (Universitas Tadulako, 2017)
Mangrove is a coastal vegetation community which dominated by several species of mangrove trees. They are able to grow and to flourish in the tidal area of muddy beach. This study aims to determine a stand and volume potency of mangrove forest in Coastal Territory of Equator village. The applied method was a partition strip. This method means to use combination between strip and partition process. On the tree level, it is used partition process while on the seedling and stake level, they are applied a small strip in the big one. The result describes that there are 5 (five) mangrove species in the spot namely Sonneratia ovata, Rhizophora mucronata, Avicennia lanata, Xylocarpus moluccensis dan Acanthus ilicifolius, particularly in Equator village. The higher INP is Avicennia lanata species which is 93, 69% level of the tree, 90,72% of the stake, and 70, 51% of seedling while the lower INP is Xylocarpus moluccensis species which is 48, 09% level of the tree, 49, 99% level of the stake and 13, 97% level of seedling. Then, it is concluded that Avicennia lanata becomes the most dominant species in mangrove forest. On the tree level potency of each hectare, Avicennia lanata species with 3, 638 m2 is higher than Xylocarpus moluccensis species with 1, and 819 m2 and the potency value of stall level is 110,25 m3/Ha. The percentage of stake volume potency of Xylocarpus moluccensis type with 0,439 m3 is lower thanAvicennia lanata type with 0, 0795 m3 in an area 10, 36 m3/Ha potency of each hectare.Keywords: Mangrove Forest Vegetation